PW 2239 A review of study designs in childhood unintentional injury prevention research in the published literature. (November 2018) - Rothman, Linda; Clements, Tessa; Macarthur, Colin
Abstract : Injury prevention research draws from many professional disciplines, with papers on the prevention of injury published in hundreds of different journals. This study examined the range of research designs used in recently published work related to child unintentional injury prevention. Hand searches of pertinent journals over the 4 year period 2013–2016 were done to identify empirical, English language, unintentional injury prevention studies in children<19 years. A previously published framework that stratified journals by the average number of injury prevention papers published/year was used to identify and randomly select 10 journals from each stratum to provide a representative sample. Studies were coded by study design, injury type, primary outcome, and type of prevention approach (education, engineering or enforcement) There were 369 studies identified; 6% were qualitative, 33% were descriptive and 59% were analytic. Of the analytic studies, 72% were observational (80% cross-sectional, 8% case control/case crossover, 8% cohort, 4% ecological). Only 28% of analytic studies were experimental, which were related primarily to transportation (80%). Transportation represented 83% of randomized control trials. The majority of studies were related to transportation (60%), all injury (14%) and burns (10%). The most common outcomes measured were non- transport injuries/fatalities (31%), reported behaviours (19%), and transport collisions/injuries/fatalities (17%). Most experimental studies evaluated educational interventions (58%). The majority of studies were in journals with impact factors between1–5 (83%), with only 8% in higher impact journals (impact factors 5–10). Recent child unintentional injury prevention research is generally descriptive or observational, cross-sectional studies in lower impact journals. There are few experimental studies evaluating interventions. Transportation studies predominate, where the injury prevention field overlaps with engineering. More rigorous study designs are needed, focusing on engineering and enforcement interventions and addressing different injury topics, to effectively reduce the population burden of childhood injury.